Noninvasive prenatal diagnosis of hemophilia A by a haplotype-based approach using cell-free fetal DNA - Chao Chen; Jun Sun; Yun Yang; Lu Jiang; Fengyu Guo; Yaping Zhu; Dan Li; Renhua Wu; Rong Lu; Mei Zhao; Fang Chen; Peixiang Ni; et al. (BioTechniques)
Aim: We aimed to demonstrate noninvasive prenatal diagnosis (NIPD) of hemophilia A (HA) using a haplotype-based approach. Methods: Two families at risk for HA were recruited for this study. First, maternal haplotypes associated with pathogenic variants were constructed using the genotypes of the mothers and probands. Then, fetal haplotypes were deduced using a maternal haplotype-assisted hidden Markov model. Finally, the NIPD results were further confirmed by invasive prenatal diagnosis. Results: Two fetal genotypes were successfully inferred, with one normal fetus and one carrier fetus. The NIPD results were confirmed by invasive prenatal diagnosis, with a 100% consistency rate. Conclusion: Our test has been shown to be accurate and reliable. With further validation in a large patient cohort, this haplotype-based approach could be feasible for the NIPD of HA and other X-linked single-gene disorders.